Bedside Gastric Ultrasonography in Term Pregnant Women Before Elective Cesarean Delivery: A Prospective Cohort Study. Issue 3 (September 2016) - Arzola, C.; Perlas, A.; Siddiqui, N.T.; Carvalho, J.A.
Abstract : ( Anesth Analg. 2015;121:752–758) Bedside ultrasonography can be used to establish the gastric contents of pregnant women about to undergo general anesthesia for elective cesarean delivery. This could help avoid the serious complication of pulmonary aspiration by prompting anesthesiologists to discourage general anesthesia in a woman found to have a full stomach. In the past ultrasonography was not able to detect an empty stomach, but technological improvements have made this a possibility. This study investigated the qualitative and quantitative sonographic patterns of the gastric antrum in fasted pregnant patients.